The Effect of Training and Workload on Employee Performance - Sundari, Eliyana; Firdaus, Muhammad Azis; Bimo, Widhi Ariyo; Maulana, Hendri; Avessina, Mohammad Jibriel (Manager : Jurnal Ilmu Manajemen, 2023)
The purpose of this study is to ascertain how employee performance is affected by workload and training. Quantitative research methodology is applied. The 110 participants who took part in this study were all employees of PT Atishar Panel. 86 people were employed in the study sample, which were randomly selected. Primary data were collected from respondents for the questionnaire used in this study. Likert scale was used. The validity and reliability tests used in this study include the traditional normality assumption test, multicollinearity, heteroscedasticity, regression analysis, and hypothesis testing. The results of the t test partially show that both the training variable (X1) and the workload variable (X2) have a positive and significant effect on employee performance (Y). Training (X1) and workload (X2) have a significant and significant effect on employee performance, according to the results of the F (simultaneous) test